Selecting velocity measurement devices: decision-making guidelines for strength and conditioning professionals - Nagatani, T.; Guppy, S. N.; Haff, G. G. (Strength and Conditioning Journal, 2025)
Velocity-based training (VBT) is a programming method that has gained increasing popularity within the strength and conditioning profession. The increased interest in VBT has led to the development of numerous velocity measurement devices, potentially creating a dilemma for strength and conditioning professionals who seek to integrate VBT into their professional practice. The aim of this review was to provide strength and conditioning professionals with practical decision-making guidelines for selecting velocity measuring devices that align with their specific training requirements. In addition, we offer a comprehensive review of the various types of velocity measurement devices currently available in the consumer market.